2017
DOI: 10.1596/1813-9450-8192
|View full text |Cite
|
Sign up to set email alerts
|

Could the Debate Be Over? Errors in Farmer-Reported Production and Their Implications for the Inverse Scale-Productivity Relationship in Uganda

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 31 publications
(47 reference statements)
6
81
3
Order By: Relevance
“…2 The second group is more concerned with the inverse farm size-productivity relationship resulting from measurement error (Lamb 2003). Using GPS-based plot area information, Gourlay, Kilic, and Lobell (2017) and Desiere and Jolliffe (2018) examined the size-productivity relationship for crop farms in Uganda and Ethiopia. Their focus was on measurement error in farm selfreported crop production, particularly with regard to the smallest farms.…”
Section: Farm Size-productivity Relationship: Natural Endowment Diffementioning
confidence: 99%
See 1 more Smart Citation
“…2 The second group is more concerned with the inverse farm size-productivity relationship resulting from measurement error (Lamb 2003). Using GPS-based plot area information, Gourlay, Kilic, and Lobell (2017) and Desiere and Jolliffe (2018) examined the size-productivity relationship for crop farms in Uganda and Ethiopia. Their focus was on measurement error in farm selfreported crop production, particularly with regard to the smallest farms.…”
Section: Farm Size-productivity Relationship: Natural Endowment Diffementioning
confidence: 99%
“…We define crop yield as total maize output (quantity) divided by maize cropping area and farm size as total cropping areas for maize production. 9 In the literature, many studies have found that measurement error on crop output and land area arise from using the selfreported data, thereby contaminating the farm size-productivity relationship (Gourlay, Kilic, and Lobell 2017;Desiere and Jolliffe 2018). However, this is not the case in China since household farms have better knowledge about the land areas in operation and their output.…”
Section: Data Collection and Variable Definitionsmentioning
confidence: 99%
“…Estimated land values are stated by the farmers for several of their fields. Additionally, there is a growing concern about recollection bias of rural production (Gourlay et al 2017, Desiere and Jolliffe 2018, Gollin and Udry 2019. To test the robustness of the relationship between farm size and incomes we use household consumption of food and beverages as alternative welfare measure for producers.…”
Section: Datamentioning
confidence: 99%
“…The process of labor reallocation from agriculture to non-agriculture has led to farm consolidation and rural prosperity in most developed countries. However, a large literature studying the relationship between farm size and productivity generally concludes that farm output declines with farm size in most developing countries (Bardhan 1973, Carter 1984, Feder 1985, Benjamin 1995, Assuncao and Braido 2007, Barrett et al 2010, Carletto et al 2013, Ali and Deininger 2015, Foster and Rosenzweig 2017, though concerns about measurement error have plagued consensus (Gourlay et al 2017, Desiere and Jolliffe 2018, Gollin and Udry 2019. The implication of an inverse farm size-productivity relationship for consumers is that food supply declines with increasing farm size.…”
Section: Introductionmentioning
confidence: 99%
“…Lamb (2003) finds evidence suggesting all of the inverse relationship between farm size and productivity can be explained by measurement error. However, others have found a more accurate measurement of farm size strengthens the inverse relationship between farm size and productivity (Carletto et al, 2013;Holden and Fisher, 2013;Gourlay et al, 2017;Desiere and Jolliffe, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%